Numerical Study of Pulsed Dielectric Barrier Discharge at Atmospheric Pressure Under the Needle-Plate Electrode Configuration - 王艳辉 叶换换 张佼 王奇 张杰 王德真 (Plasma science & technology, 2016)
In this paper, we study the characteristics of atmospheric-pressure pulsed dielectric barrier discharge （DBD） under the needle-plate electrode configuration using a one-dimensional self-consistent fluid model. The results show that, the DBDs driven by positive pulse, negative pulse and bipolar pulse possess different behaviors. Moreover, the two discharges appearing at the rising and the falling phases of per voltage pulse also have different discharge regimes. For the case of the positive pulse, the breakdown field is much lower than that of the negative pulse, and its propagation characteristic is different from the negative pulse DBD. When the DBD is driven by a bipolar pulse voltage, there exists the interaction between the positive and negative pulses, resulting in the decrease of the breakdown field of the negative pulse DBD and causing the change of the discharge behaviors. In addition, the effects of the discharge parameters on the behaviors of pulsed DBD in the needle-plate electrode configuration are also studied.